The Role of Responsibility Accounting in Cost Control in Some Sectors: Literature Review - Lina Rosyidah; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2025)
This study seeks to examine the role of responsibility accounting in cost control, with a focus on cost centers. Responsibility accounting helps organizations control costs by assigning cost responsibility to each cost center manager. Through this system, costs incurred can be monitored, controlled and reported accurately. This study uses a literature review method from various empirical studies that examine The implementation of responsibility accounting in the responsibility accounting process is underway public and private sectors. The results of this study indicate that the implementation of responsibility accounting is effective in cost centers is able to increase operational efficiency and minimize budget deviations. However, challenges in separating controlled and uncontrolled costs as well as limited organizational structures in some companies are still obstacles to the effectiveness of cost control. This study highlights the importance of cost segregation and active management participation in budgeting to improve cost center performance.